Productivity improvements in metal furniture industry / Norazira Mohd Sayuti - Mohd Sayuti, Norazira (2010)
The research has been done to study the productivity improvement in metal furniture industry. The objective of this study was to improve process capability and stability of cutting and punching machine. To productivity improvement, companies should be suggestion of proper recording of data, reduction in time required and identify of process capability and stability at cutting and punching operation. The data collected were compiled and analysed by using variable control charts whether the processes are statistically within control. Using variable control charts to identify averages and ranges of times out of control or in control required the result. It is recommended that to productivity improvement the company should maintain equipment and machinery, workers training, using semi-auto operation to reduce time taken, data record and never ending continuous improvement.